Analysis of the Economic Impact of Sharia Cooperatives on the Empowerment of Rural Women - Ahmad Febri Kurniawan; Pitri Wahyuni (Jurnal Ekonomi islam and Manajemen, 2025)
Sharia cooperatives in rural Indonesia present a promising alternative for inclusive finance, yet their specific impact on women’s empowerment remains critically under-researched. This study measures the economic effects of women’s participation in these cooperatives, focusing on income enhancement, asset ownership, and decision-making autonomy. Employing a mixed-methods approach, quantitative data from 200 women members across rural Java were analyzed alongside qualitative insights from focus group discussions (FGDs) and in-depth interviews. Results demonstrate that sustained participation (≥2 years) significantly increased average monthly income by 43% and productive asset ownership by 28%, primarily through access to profit-sharing financing (mudharabah) and cooperative-led entrepreneurship training. Critically, 82% of participants reported greater influence in household financial decisions, indicating enhanced agency. However, structural barriers persist: low financial literacy (only 35% understood basic sharia contracts) and deep-rooted patriarchal norms limited full economic engagement. Qualitative themes revealed that male relatives often controlled loan utilization despite women’s nominal ownership. These findings necessitate a gender-responsive empowerment model integrating three pillars: 1) Sharia-compliant financial literacy modules, 2) Cooperative governance reforms ensuring women’s leadership roles, and 3) Community dialogues challenging socio-cultural constraints. The study confirms sharia cooperatives’ potential as empowerment vehicles but underscores that inclusive impact requires deliberate institutional design addressing gendered barriers.